2022
DOI: 10.3847/2041-8213/ac88bf
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of γ-Ray Pulsations from PSR J1835–3259B in the Globular Cluster NGC 6652

Abstract: Motivated by the recent discovery of the pulsar J1835−3259B with a spin period 1.83 ms in the globular cluster (GC) NGC 6652, we analyze the γ-ray data obtained with the Large Area Telescope on board the Fermi Gamma-ray Space Telescope (Fermi) for the GC and detect the pulsations of this millisecond pulsar (MSP) at a 5.4σ confidence level (the weighted H-test value is ∼41). From timing analysis of the data, a pulse profile that is similar to the radio one is established. We thus consider that we have detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…Then in NGC 6626 (M28), significances of ∼4.3σ and 5.4σ γ-ray pulsations were respectively reported for PSR B1821−24 by Wu et al (2013) and Johnson et al (2013). Very recently, Zhang et al (2022) reported the detection of γray pulsations (at a 5.4σ significance level) of a newly discovered MSP J1835−3259B in NGC 6652 (Gautam et al 2022). The properties of these three MSPs are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 95%
“…Then in NGC 6626 (M28), significances of ∼4.3σ and 5.4σ γ-ray pulsations were respectively reported for PSR B1821−24 by Wu et al (2013) and Johnson et al (2013). Very recently, Zhang et al (2022) reported the detection of γray pulsations (at a 5.4σ significance level) of a newly discovered MSP J1835−3259B in NGC 6652 (Gautam et al 2022). The properties of these three MSPs are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 95%
“…In order to separate a known pulsar's emission from that of the host GC, we carried out the similar data analysis for NGC 6624 and NGC 6626 as for NGC 6341. The analysis results for NGC 6652 were taken from that reported in Zhang et al (2022).…”
Section: Data Analysis For Three Known Gc γ-Ray Mspsmentioning
confidence: 99%
“…Pulse-phase resolved analysis for the emission of NGC 6652 was conducted by Zhang et al (2022), and in a small off-pulse phase range they defined, no emission was detected (TS 1). Using the results, we calculated a TS map in 0.1-500 GeV and include it in Figure 6.…”
Section: Phase-resolved Analysismentioning
confidence: 99%
See 2 more Smart Citations